A Comprehensive Pharmacognostic, Phytochemical Description, and Clinical Implementation of Amaranthus viridis - Jaafar, Noor Sabah; Enas J. Kadhim (Iraqi Journal of Pharmaceutical Sciences, 2025)
The pigweed family, Amaranthaceae, includes Amaranthus viridis, popularly known as green amaranth. This herb grows quickly and has an annual lifespan. Traditionally, it has been used to treat anemia, eczema, bronchitis, inflammation, and leprosy. Additionally for respiratory issues, ocular conditions, and asthma. The phytochemical analysis of Amaranthus viridis L extracts identifies the presence of several categories of biologically active substances (phytochemicals): phenolics, which include flavonoids, tannins, and phenolic acids. Alkaloids, cardiac glycosides, various classes of triterpenoids, and steroids were also found. Numerous investigations on A. viridis have been conducted to explore its pharmacological range. The majority of research identified laxative, hepatoprotective, analgesic, anti-inflammatory, antitumor, antimicrobial, anti-diabetic, antitumor, wound healing, and antioxidant properties. The goal of the current review of the literature is to give extensive information on the morphological traits, folk usage, phytochemicals, and pharmacological properties of Amaranthus viridis.